Particle radiotherapy and molecular therapies: mechanisms and strategies towards clinical applications. (1st February 2022) - Helm, Alexander; Fournier, Claudia; Durante, Marco
Abstract: Immunotherapy and targeted therapy are now commonly used in clinical trials in combination with radiotherapy for several cancers. While results are promising and encouraging, the molecular mechanisms of the interaction between the drugs and radiation remain largely unknown. This is especially important when switching from conventional photon therapy to particle therapy using protons or heavier ions. Different dose deposition patterns and molecular radiobiology can in fact modify the interaction with drugs and their effectiveness. We will show here that whilst the main molecular players are the same after low and high linear energy transfer radiation exposure, significant differences are observed in post-exposure signalling pathways that may lead to different effects of the drugs. We will also emphasise that the problem of the timing between drug administration and radiation and the fractionation regime are critical issues that need to be addressed urgently to achieve optimal results in combined treatments with particle therapy.